ANALYZE THE PRONUNCIATION ERRORS OF ENGLISH CONSONANTS IN STUDENTS MAJORING IN ARABIC EDUCATION - Jihan Luthfi; Wulandari; Yani Lubis (Cemara Education and Science, 2025)
Although the primary goal of learning English as a second language is to be able to communicate effectively in the target language, the language competency desired by learners and teachers is dependent on the reason for studying that language. The English language has 24 consonants, while Arabic has 28. English consonants are grouped based on where and how they are pronounced. In contrast to vowels, which are formed by allowing air to flow freely from the lungs via the lips, consonants are produced by forcing the airstream out and can be voiced or devoiced. This study shows that although students have difficulty pronouncing words in English, they have a basic understanding of common words. Obstacles in learning English for Arabic students, especially in the context of consonant pronunciation, are the main focus. These findings give us an idea that English is a little difficult to understand, especially for Arabic students..